Gut Microbiome and Serum Metabolome Analyses Identify Unsaturated Fatty Acids and Butanoate Metabolism Induced by Gut Microbiota in Patients With Chronic Spontaneous Urticaria - Wang, Detong; Guo, Shuping; He, Hongxia; Gong, Li; Cui, Hongzhou (Frontiers in Cellular and Infection Microbiology, 2020)
Chronic urticaria (CU) is defined as the continuous or intermittent presence of urticaria for a period exceeding 6 weeks and sometimes occurring with angioedema. Between 66 and 93% of patients with CU have chronic spontaneous urticaria (CSU), the precise pathogenesis of which is largely unknown. The aim of this study was to determine the relationship between gut microbiota and serum metabolites and the possible pathogenesis underlying CSU. We collected feces and blood samples from CSU patients and healthy controls and the relationship between gut microbiota and serum metabolites was assessed using 16S rRNA gene sequencing and untargeted metabolomic analyses. The CSU group exhibited decreased alpha diversity of the microbial population compared to the control group. The abundance of unidentified Enterobacteriaceae was increased, while the abundance of Bacteroides, Faecalibacterium, Bifidobacterium, and unidentified Ruminococcaceae was significantly reduced in CSU patients. The serum metabolome analysis revealed altered levels of docosahexaenoic acid, arachidonic acid, glutamate, and succinic acid, suggesting changes in unsaturated fatty acids and the butanoate metabolism pathway. The combined serum metabolomics and gut microbiome datasets were correlated; specifically, docosahexaenoic acid, and arachidonic acid were positively correlated with Bacteroides. We speculate that alterations in gut microbes and metabolites may contribute to exacerbated inflammatory responses and dysregulated immune function with or without regulatory T cell dependence in the pathogenesis of CSU.